SpeedFlower: a comprehensive speed breeding protocol for indica and japonica rice - Kabade, Pramod Gorakhanath; Dixit, Shilpi; Singh, Uma Maheshwar; Alam, Shamshad; Bhosale, Sankalp; Kumar, Sanjay; Singh, Shravan Kumar; Badri, Jyothi; Varma, Nadimpalli Rama Gopala; Chetia, Sanjay; Singh, Rakesh; Pradhan, Sharat Kumar; et al. (Wiley, 2024)
To increase rice yields and feed billions of people, it is essential to enhance genetic gains. However, the development of new varieties is hindered by longer generation times and seasonal constraints. To address these limitations, a speed breeding facility has been established and a robust speed breeding protocol, SpeedFlower is developed that allows growing 4–5 generations of indica and/or japonica rice in a year. Our findings reveal that a high red-to-blue (2R > 1B) spectrum ratio, followed by green, yellow and far-red (FR) light, along with a 24-h long day (LD) photoperiod for the initial 15 days of the vegetative phase, facilitated early flowering. This is further enhanced by 10-h short day (SD) photoperiod in the later stage and day and night temperatures of 32/30 °C, along with 65% humidity facilitated early flowering ranging from 52 to 60 days at high light intensity (800 μmol m−2 s−1). Additionally, the use of prematurely harvested seeds and gibberellic acid treatment reduced the maturity duration by 50%. Further, SpeedFlower was validated on a diverse subset of 198 rice accessions from 3K RGP panel encompassing all 12 distinct groups of Oryza sativa L. classes. Our results confirmed that using SpeedFlower one generation can be achieved within 58–71 days resulting in 5.1–6.3 generations per year across the 12 sub-groups. This breakthrough enables us to enhance genetic gain, which could feed half of the world's population dependent on rice.